Perbandingan Kinerja Keuangan Sebelum dan Sesudah Initial Public Offering (Studi Kasus pada PT Wijaya Karya Bangunan Gedung Tbk Tahun 2014-2020) - Ayu Rizkia Nur Nabilah; Endang Hatma Juniwati; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine whether there is a significant difference between the financial performance of PT Wijaya Karya Bangunan Gedung Tbk before and after conducting an Initial Public Offering (IPO). The indicators used in this study are financial ratios including Current Ratio (CR), Working Capital to Total Assets Ratio (WCTA), Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Inventory Turnover (TATO), Return on Investment (ROI), and Return on Equity (ROE). The data used is the annual financial report of PT Wijaya Karya Bangunan Gedung Tbk for 2014-2020. The data analysis method used is the Paired Sample T Test and the Wilcoxon Signed Ranks Test. The results showed that there were significant differences in ROE, while in CR, WCTA, DAR, DER, ITO, TATO, and ROI there were no significant differences.